1990
DOI: 10.1037/0021-843x.99.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiologic responses to combat imagery of Vietnam veterans with posttraumatic stress disorder versus other anxiety disorders.

Abstract: We used psychophysiologic techniques to assess responses to imagery of psychologically stressful past experiences in medication-free Vietnam combat veterans classified, on the basis of DSM-III-R criteria into posttraumatic stress disorder (PTSD; n = 7) or non-PTSD anxiety disorder (anxious; n = 7) groups. Scripts describing each individual's combat experiences were recorded and played back in the laboratory. Ss were instructed to imagine the events the scripts portrayed while heart rate, skin conductance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
3
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 17 publications
10
172
3
4
Order By: Relevance
“…Lower physiological reactivity in the high dissociation group is surprising in light of the fact that most of the members of this group had PTSD symptoms. This finding contrasts with previous findings of generally higher physiological reactivity in subjects with PTSD (23)(24)(25)(26). The response of subjects in the high dissociation group may provide evidence of a specific PTSD subtype of highly dissociative individuals who may respond with a general physiological numbness.…”
Section: Discussioncontrasting
confidence: 56%
“…Lower physiological reactivity in the high dissociation group is surprising in light of the fact that most of the members of this group had PTSD symptoms. This finding contrasts with previous findings of generally higher physiological reactivity in subjects with PTSD (23)(24)(25)(26). The response of subjects in the high dissociation group may provide evidence of a specific PTSD subtype of highly dissociative individuals who may respond with a general physiological numbness.…”
Section: Discussioncontrasting
confidence: 56%
“…A number of studies (Pitman et al, 1987(Pitman et al, , 1990Blanchard et al, 1982;McFall et al, 1990;Orr et al, 1993;Shin et al, 1999) have investigated psychophysiological reactivity to trauma-related scripts in patients with PTSD. In contrast to the present study, most former studies found more pronounced heart rate responses in PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to replicate the findings of larger heart rate responses to traumatic reminders in patients with PTSD. Heart rate differences in response to trauma-related imagery were found in combat-related PTSD in male veterans (Pitman et al, 1987(Pitman et al, , 1990Blanchard et al, 1982;McFall et al, 1990;Orr et al, 1993) and abuse-related PTSD in female patients (Shin et al, 1999;Carson et al, 2000;Orr et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When individuals with PTSD underwent cued recall of trauma, or were exposed to reminders that triggered involuntary traumatic memories, increased heart rate (HR), a sign of emotional arousal (Blechert, Michael, Grossman, Lajtman, & Wilhelm, 2007), has consistently been found (e.g. Arditi-Babchuk, Feldman, & Gilboa-Schechtman, 2009; O’Kearney & Parry, 2014; Pitman et al, 1990). …”
Section: Heart Rate As An Index Of Emotional Arousalmentioning
confidence: 99%